2010
DOI: 10.2478/s11535-010-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Vitis vinifera L. cv. ‘Malagouzia’ and ‘Xinomavro’

Abstract: Abstract:The effects of six basal media on in vitro shoot proliferation of the greek grapevines Vitis vinifera L. cv. 'Malagouzia' and 'Xinomavro' were investigated. Galzy and Zlenco proved to be the most effective for 'Malagouzia' and 'Xinomavro', respectively. If only BA was present in the medium, shoot development was poor and the plantlets were chlorotic. When the medium was supplemented with BA and NAA, growth was enhanced. The best ratio (in μM) of growth regulators was 0.5/0.3 for 'Malagouzia', and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The author used leaf explants as starting material and found that the highest plantlet number and growth rate were obtained using 1 / 5 Linsmaier-Skoog medium supplemented with a combination of BA (0.02 mg/L) and 2-naphthaleneacetic acid (0.01-0.10 mg/L). Although several authors have reported a synergistic effect between cytokinins and auxins during shoot proliferation [15,16], in this work culture media combining BA or Zea (0.1 mg/L) with IBA (0.01 mg/L) were not effective in enhancing proliferation (P≥0.05) (Figure 2), which is in good agreement with the results obtained for P. lusitanica [10].…”
Section: Shoot Proliferation and Rootingsupporting
confidence: 91%
“…The author used leaf explants as starting material and found that the highest plantlet number and growth rate were obtained using 1 / 5 Linsmaier-Skoog medium supplemented with a combination of BA (0.02 mg/L) and 2-naphthaleneacetic acid (0.01-0.10 mg/L). Although several authors have reported a synergistic effect between cytokinins and auxins during shoot proliferation [15,16], in this work culture media combining BA or Zea (0.1 mg/L) with IBA (0.01 mg/L) were not effective in enhancing proliferation (P≥0.05) (Figure 2), which is in good agreement with the results obtained for P. lusitanica [10].…”
Section: Shoot Proliferation and Rootingsupporting
confidence: 91%
“…Hence, developing an efficient in vitro technique for the propagation of pomegranate is of great importance. During the past decade, tissue culture techniques have been widely used for the propagation of some important tropical and subtropical fruit trees (Agarwal et al 2004;Tsukamoto et al 2007;PerezTornero et al 2010;Skiada et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that shoot proliferation and rooting efficiency in Vitis spp. are affected by the type and concentration of cytokinin and auxin (Gray and Benton, 1991;Skiada et al, 2010). The efficiency of in vitro propagation can differ based on the genetic characteristics of the species, making it important to test their effects and to select the optimal PGR conditions.…”
Section: Effects Of Plant Growth Regulators For Root Induction and Acclimatizationmentioning
confidence: 99%